2003
DOI: 10.1081/ss-120016578
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption Rate and Solubility in Monoethanolamine/Piperazine/Water

Abstract: The solubility and absorption rate of carbon dioxide into monoethanolamine/ piperazine/water were measured in a wetted wall column at 40-60°C. The total amine concentration was varied from 1.0 M to 5.0 M with monoethanolamine blends containing 0 to 1.2 M piperazine. CO 2 solubility and solution speciation were simulated by nine equilibrium reactions. Two of the equilibrium constants were adjusted to match literature data. The rate of absorption was predicted by the theory of diffusion with fast chemical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 12 publications
1
76
2
1
Order By: Relevance
“…This approach is in agreement with Bishnoi et al, [38], Dang and Rochelle [39], Cullinane et al, [40] and Khalili et al, [41] that also proposed the used of piperazine as an activator to other slower alkanolamines such as MDEA. It was also reported that piperazine has a rapid reaction rate with CO 2 than MEA [42], [43].…”
Section: Carbon Dioxide Removalsupporting
confidence: 80%
“…This approach is in agreement with Bishnoi et al, [38], Dang and Rochelle [39], Cullinane et al, [40] and Khalili et al, [41] that also proposed the used of piperazine as an activator to other slower alkanolamines such as MDEA. It was also reported that piperazine has a rapid reaction rate with CO 2 than MEA [42], [43].…”
Section: Carbon Dioxide Removalsupporting
confidence: 80%
“…In previous work, research at the University of Texas defined the actual energy, ideal/theoretical energy, and lost work involved with MEA absorption and stripping approaches (Rochelle, 2003). The result was that more than half of the energy required by a standard MEA and CO 2 compression approach was the result of lost work; losses in the MEA stripper were the largest (~70% of total).…”
Section: Research Objectivesmentioning
confidence: 99%
“…Previous research suggested that more than half of the energy required by a standard MEA and CO 2 compression approach was the result of lost work; losses in the MEA stripper were the largest (Rochelle, 2003). Several innovative processing approaches were proposed to reduce this lost work by up to 20%; in general, these approaches involved integrating the need for heat in the MEA stripper with the needs of the CO 2 compression train and reducing temperature approaches in the lean/rich exchanger.…”
Section: Process Configurationsmentioning
confidence: 99%
“…MEA has been blended with amines that are less corrosive and require less steam to regenerate such as MEA/2-amino-2-methyl-1-propanal (AMP) (Dey and Aroonwilas, 2009) and MEA/MDEA (Idem et al, 2006). The additive piperazine (PZ) in MEA solutions was able to accelerate CO 2 absorption and allows use of lower MEA concentrations (Dang and Rochelle, 2003;Dugas and Rochelle, 2011). Freeman et al, 2010 proposed new amine solvent, i.e., concentrated aqueous piperazine (PZ), which has an absorption rate that is higher than MEA.…”
Section: Chemical Absorptionmentioning
confidence: 99%